Density and Molar Volume of Bismuth Oxide Doped Lithium Lead Borate Glass System. (February 2020) - Kolavekar, Sangeeta B.; Ayachit, N. H.
Abstract: This work mainly focuses on the study of the density and molar volume of bismuth oxide doped lithium lead borate coded as LPBB glass system. These glasses were prepared by conventional melt quench method, in order to study their structure. Variation in the value of both density and molar volume as the mole concentration of bismuth content in lead-borate glasses was studied. Variation of density of present glasses is exactly opposite to that of molar volume with increasing mole concentration of bismuth oxide. The F.T.I.R Analysis of LPBB glasses discovered that the network structure mainly depends on the BO3 and BO4 units. Because of the role played by PbO as a glass modifier the transformation of [BO3] units to [BO4] units takes place.